Excitonic contribution on light emitting properties of nanosilicon - Ghoshal, Sib Krishna (2011)
A phenomenological model is developed by integrati ng the effect of excitonic energy states, localized surface states and quantum confin ement (QC) to obtain an analytical expression for the room temperature photoluminescence (PL) int ensity. We calculate the binding energy of strongly confined excitons in silicon (Si) quantum dots (QD) having sizes 1 to 7.75 nm to examine its contribution on optical band gap and el ectronic properties. The band gap with excitonic contribution is found to decrease as much as 0.23 eV for the smallest dot. The effect of exciton states explains almost accurately the exper imental PL data. Our model provides the mechanism for controlling the PL intensity through fitting parameters. Huge excitonic effects, which depend strongly on QD size and shape, charact erize the optical spectra. The results for the size dependence of the optical band gap, the PL int ensity, and oscillator strength are presented the role excitonic effects on optical and electroni c properties are discussed.